Financial Stress and Subjective Wellbeing among Children -Evidence from Finland - Lindberg Marja; Nygård Mikael; Nyqvist Fredrica; Hakovirta Mia (Springer Link, 2022)
In this article we analyse how subjective wellbeing amongst Finnish children is associated with experiences of financial stress, that is, worries about money and one’s financial situation. We focus on both affective and cognitive components of subjective wellbeing in order to receive a broader understanding on children’s subjective wellbeing. We use Finnish data from the International survey of children’s lives conducted by the Children’s Worlds Project during the years 2013–2014. The results show that experienced financial stress is negatively and more strongly associated with cognitive subjective wellbeing than with affective subjective wellbeing, even when controlling for socioeconomic and other factors found to be influential for subjective wellbeing in previous research.